Cabenuva: A breakthrough in HIV/AIDS treatment - Duaa Zafar (Journal of the Pakistan Medical Association, 2023)
Madam, HIV (human immunodeficiency virus) and AIDS (acquired immunodeficiency syndrome) persist as risks to public health despite rigorous efforts to control the crisis. Pakistan, as a low-income country, experiences a greater incidence of new HIV cases, a significant public health concern.1 Only 14% of people living with HIV/AIDS are aware of their status, with a mere 10% undergoing treatment while statistics on viral suppression are absent.1 Predictably, the country is falling behind in achieving its 90-90-90 target set by the Joint United Nations Programme on AIDS/HIV (UNAIDS).1 In January 2021, Cabenuva received the U.S. Food and Drug Administration (FDA) approval (cabotegravir and rilpivirine, extended-release formulations) to be administered monthly for the management of HIV-1 infection in adults on consistent antiretroviral therapy (ART) and are virologically suppressed, making it the first of its kind.2 Vocabria (Cabotegravir) and Edurant (rilpivirine) tablet dosage forms were also approved by the FDA to be taken once a month for tolerability before switching to the intravenous drug.2 The results of the two randomized, open-label control trials- ATLAS and FLAIR, demonstrate that the monthly cabenuva effectively maintains HIV-1 suppression in patients when compared to oral ART.3 Moreover, the eight-week cabenuva regimen has the same outcome as the four-week one, according to the ATLAS trial.3 Thus, the injectable treatment decreases the need for regular ingestion while increasing compliance and may help patients with HIV-associated stigma.3 Additionally, it is more likely to reduce toxic adverse effects and resistance linked with poor oral abidance, a promising option to control HIV infection.3 The global burden of the COVID-19 pandemic has exhausted resources allocated for HIV prevention, testing and access to ARTs, as well as long-term HIV management and mental health.4 It is paramount that we find innovative ways to tackle the HIV epidemic in Pakistan. One way we can do so is by introducing cabenuva as a treatment option and a substitute for oral ART. The drug can encourage more people to get and stay on treatment, as a once-a-month routine is preferable to multiple daily tablets. Secondly, it may decrease anxiety and depression linked with daily consumption to improve the quality of life for those living with HIV/AIDS. Indeed, this regimen may assist in combating the high dropout rates from previous treatments and offer more choices to patients so that Pakistan achieves its UNAIDS goal by 2030.